HUBUNGAN KUALITAS TIDUR DENGAN MEMORI JANGKA PENDEK (SHORT-TERM MEMORY) PADA PELAJAR KELAS XII SMA KRISTEN BASIC BATAM - Susana, Elvita Nora; Sahreni, Sukma; Gulo, Chandra Pratama (Universitas Batam, 2023)
Background: : Sleep is defined as a subconscious state where a person can still be awakened by providing sensory stimulation or other stimuli. Sleep is also a form or way to relieve one's physical or mental fatigue. Sleep quality can affect brain function in concentrating and recalling knowledge storage or also called memory. Methods: The method used is Observational Analytics. The sample in this research isThere are 57 class XII students at Batam Basic Christian High School in 2023. Sampling used total sampling technique. Data collection techniques use observation and questionnaires. The data analysis technique uses Chi-Square Test. Results: There is a relationship between sleep quality and short-term memory where the results obtained are good sleep quality, there are 78.3% of respondents who have high short-term memory, 21.7% have medium short-term memory, and 0% who have low short term memory. Of respondents with poor sleep quality, 20% had high short-term memory, 36% had medium short-term memory, and 44% had low short-term memory. Conclusion: It can be concluded that there issignificant relationship between sleep quality and short-term memory in class XII students of Batam Basic Christian High School in 2023 with a p-value = 0.000.